Duty, Passion and the (Re)Production of a Gendered Life: One Young Woman's Struggle to Craft a Meaningful Vocational Project - Ahola-Sidaway, Janice; McKinnon, Margaret (Atlantis, 2006)
This longitudinal narrative case study traces one young woman's vocational journey from age 17 to 23. Drawing on youth transitions literature and feminist scholarship on the gendered division of labour, the paper considers how her journey was shaped by powerful ideologies linked to relational work, home-based production, and postsecondary schooling.